2007
DOI: 10.1001/archpedi.161.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multisource Feedback on Resident Communication Skills and Professionalism

Abstract: A multisource feedback intervention positively affected communication skills and professional behavior among pediatric residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
161
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(169 citation statements)
references
References 27 publications
1
161
0
7
Order By: Relevance
“…Therefore, the third-year residents probably were never given feedback from patients' families and nurses and therefore may not have made the expected improvements during residency. Brinkman et al 14 confirmed this possibility when they demonstrated that a feedback intervention after multisource evaluation (ie, 360-degree method) improved communication skills and professional behavior of pediatrics residents. In contrast, Weigelt et al 15 concluded that the 360-degree evaluation system was more time intensive to conduct and did not enhance the evaluation of surgical residents.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the third-year residents probably were never given feedback from patients' families and nurses and therefore may not have made the expected improvements during residency. Brinkman et al 14 confirmed this possibility when they demonstrated that a feedback intervention after multisource evaluation (ie, 360-degree method) improved communication skills and professional behavior of pediatrics residents. In contrast, Weigelt et al 15 concluded that the 360-degree evaluation system was more time intensive to conduct and did not enhance the evaluation of surgical residents.…”
Section: Discussionmentioning
confidence: 96%
“…While there is no clear, concise, and currently relevant description of professionalism, many residency programs have introduced the role-modeling methods and feedback from patients, attending physicians, nurses, and their peers [5][6][7]. Other programs have incorporated reflective practice to increase awareness [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…1 While professionalism is hard to objectively measure and difficult to teach, there has been progress in areas like patient confidentiality (e.g., the Health Insurance Portability and Accountability Act), communication skills, interactions with pharmaceutical companies, law and ethics. [2][3][4][5][6][7][8][9][10][11][12] However, despite extensive research and debate, it remains difficult to define or measure the domain that the ACGME calls the "professional accountability to society." 1,10,[13][14][15][16] Further, in this age of Internet communication, the identity of being a 'professional" is expanding, inadvertently blurring the interface between work and personal time.…”
Section: Introductionmentioning
confidence: 99%